Improvement of Soundscapes Based on Noise Control in Urban Forest as an Effort to Fulfill Quality of Green Open Space Standards - suyatno suyatno; Lailatul Inayah; Susilo Indrawati (Jurnal Fisika dan Aplikasinya, 2022)
Urban forests play an important role in green open spaces. Urban forests have aesthetic functions and social functions that refer to the quality standards. Urban noise causes city forest soundscapes to be less comfortable and less aesthetic so that its function as a green open space is not fulfilled. This study aims to improve the quality of sound in urban forests (soundscape) based on the quality of green open space standards through noise control and find out the type of improvement most preferred by visitors. The quality of standard of green open space is pursued through sound masking, active noise cancellation, and convolution in sound signal conditioning. The convoluted sound signal is traffic noise with a convolved signal in the form of bird noise, water rush, and relaxation music. From the results of the improvement of the sound signal then tested on 30 respondents through a comparison test method. The subjective acoustic parameters of the environment are identified, which includes the value of the autocorrelation function (τ1, φ1) and dynamic range (DR). Efforts to improve the quality of acoustics based on the quality of green open space the most preferred by respondents were sound masking and ANC with birdsong with successive scores 4.44 and 2.78. The results of identification of traffic noise treated by ANC and sound masking with songbird obtained values DR = 32.35 dBA, τ1 = 0.73 s, and φ1 = 0.03. These parameters describe these sounds tend to be preferred because the human ear is more sensitive with high pitch and DR.